Validitas dan Praktikalitas Permainan Kartu Kimia (C-Card) pada Materi Sistem Koloid sebagai Media Pembelajaran kelas XI SMA/MA - Aulia Zebina; Bayharti Bayharti (Universitas Negeri Padang, 2020)
The purpose of the research to develop learning media for chemical card games (C-Card) on colloidal system materials for grade XI SMA / MA and determine the level of validity and practicality of the developed media. This research uses a 4-D model which consists of 4 stages, namely definition, design, development and dissemination. The resulting media was validated by two chemistry lecturers at the faculty of mathematics and natural sciences UNP and also by the two chemistry teachers at SMAN 1 Batang Anai. Through a validation questionnaire, the validation value of kappa moment obtained was 0.85 with a very high category and value of the practicality of teachers and students was 0,88 with very high categories an 0.80 with high categories. It can be concluded that the chemical card game media is valid and practical.